If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + 5 = 8 Reorder the terms: 5 + 3c = 8 Solving 5 + 3c = 8 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3c = 8 + -5 Combine like terms: 5 + -5 = 0 0 + 3c = 8 + -5 3c = 8 + -5 Combine like terms: 8 + -5 = 3 3c = 3 Divide each side by '3'. c = 1 Simplifying c = 1
| 2b+8=22 | | 6a+20=9a-36 | | 3y+4=7 | | 10x=(8x+32) | | 2a+5=21 | | 8t=-68 | | 3x^2+10x-7=0 | | 2u+5=25 | | 4(5x+2)-4=0 | | 3x^2-15x=-6 | | X+89= | | 7a=4-b | | 4-5x=444 | | 4x^2-3+8=0 | | 5(s+9)-52= | | 2x*3x=144 | | X+109= | | 15x-5y=26 | | 22+6p=4+12p | | 49x^2-26X+36=0 | | 8x-6=9x+2 | | 5x^2+39x-54=0 | | 18=11y-8y | | N+0.48=12.7 | | 24x-1= | | -2x-2x=31-7 | | x^3+12x^2+32x=0 | | -5+(-15+1)=2(7d-16)-d | | 20x+5= | | y=-7+3 | | 15+2a=8+3a | | s^2-8s+8=0 |